1995
DOI: 10.1021/ja00151a035
|View full text |Cite
|
Sign up to set email alerts
|

Upon the Chemical Origin of Exchange Couplings in d2 Systems

Abstract: In the mid-1980s two major events renewed interest in the interaction between dihydrogen and transition metals. The most important was the discovery by Kubas that dihydrogen can coordinate to a transition metal without being dissociated.'s2 Besides this major discovery, another new phenomenon was reported by two groups, namely, the existence of large, temperature-dependent H-H couplings in some transition metal p~lyhydrides.~.~ The quantum mechanical origin of these couplings was independently recognized by Zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
43
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 0 publications
9
43
0
Order By: Relevance
“…Rotation of the dihydrogen ligand around the M−H 2 bond axis must be rapid on the chemical shift time scale. This is quite reasonable, since reported barriers to hydrogen rotation are very low, except in d 2 systems. , A second process exchanges hydrogen nuclei between the dihydrogen and the hydride ligands. Since our complexes are positively charged, it seems reasonable to speculate that a proton transfer may be involved, although it has been reported that the hydride ligands of the closely related ruthenium complexes Tp Me 2 Ru(PR 3 )(H 2 )H also exchange rapidly on the NMR time scale.…”
Section: Discussionmentioning
confidence: 56%
“…Rotation of the dihydrogen ligand around the M−H 2 bond axis must be rapid on the chemical shift time scale. This is quite reasonable, since reported barriers to hydrogen rotation are very low, except in d 2 systems. , A second process exchanges hydrogen nuclei between the dihydrogen and the hydride ligands. Since our complexes are positively charged, it seems reasonable to speculate that a proton transfer may be involved, although it has been reported that the hydride ligands of the closely related ruthenium complexes Tp Me 2 Ru(PR 3 )(H 2 )H also exchange rapidly on the NMR time scale.…”
Section: Discussionmentioning
confidence: 56%
“…However, when the H 2 is rotated 90°, the σ* orbital does not find any occupied d orbital in the metal to interact so that the back-donation is completely lost in complex 3 , which therefore has a remarkably high energy. Recent experimental findings support this analysis . In these works it has been observed that the H 2 rotation in the [(Cp) 2 M(η 2 -H 2 )L] (M = Ta, Nb; L = several π acceptor ligands) complexes has a large rotational barrier (ca.…”
Section: Resultsmentioning
confidence: 75%
“…H NMR spectra for the hydride region of a mixture of 1 and 1-d 1 at various temperatures as reported by SaboEtienne and coworkers. 18 The signal designated as c is due to 1 and is invariant with temperature. The signals designated as b and c are due to 1-d 1 .…”
Section: Dihydrogen Complexes With An Adjacent Hydride Ligandmentioning
confidence: 99%
“…In contrast the HD complex 1-d 1 exhibits decoalescence at low temperature, allowing the two ends of the bound HD ligand to give distinct resonances (Scheme 1). 18 This profound change in the NMR spectrum upon isotope substitution is not the result of a conventional KIE on the rotation process. Rather, Chaudret and coworkers attribute this to the quenching of QMEC by isotope substitution.…”
mentioning
confidence: 99%